The dynamic behaviour of a buried water pipe and its effect on leak location using acoustic methods - Almeida, Fabricio; Joseph, Phillip; Brennan, Michael [UNESP]; Whitfield, Stuart; Dray, Simon (Trans Tech Publications, 2013)
Leakage in buried pipes is one of the main concerns for water companies due to the scarcity of potable water sources. Older metallic pipelines have been replaced by plastic pipes in such systems, which makes it more difficult to locate leaks using acoustics and vibration. This is mainly because of the high attenuation of leak signals caused by the damping in the pipe wall. To investigate acoustic methods in leak location in controlled conditions, a bespoke test rig was constructed in the UK. In this paper, data from this test-rig is used to discuss some issues that arise when using two contemporary correlators. Of particular interest, is the way in which a resonance in the system can have a profound effect on the estimate of the position of the leak depending on the way in which the leak noise signals are processed. © (2013) Trans Tech Publications.
Keywords: Acoustic methods; Buried plastic pipes; Leak detection; Acoustic method; Buried pipes; Controlled conditions; Dynamic behaviours; Leak locations; Leak signals; Noise signals; Water companies; Correlators; Damage detection; Plastic pipe; Potable water; Water pipelines